Environmental Enrichment Rescues Visually-Mediated Behavior in Ten-m3 Knockout Mice During an Early Critical Period - Blok, James; Black, Dylan A.; Petersen, Justin; Sawatari, Atomu; Leamey, Catherine A. (Frontiers in Behavioral Neuroscience, 2020)
Environmental enrichment (EE) has been shown to promote neural plasticity. Its capacity to induce functional repair in models which exhibit profound sensory deficits due to aberrant axonal guidance has not been well-characterised. Ten-m3 knockout (KO) mice exhibit a highly-stereotyped miswiring of ipsilateral retinogeniculate axons and associated profound deficits in binocularly-mediated visual behaviour. We determined whether, and when, EE can drive functional recovery by analysing Ten-m3 KO and wildtype mice that were enriched for 6 weeks from adulthood, weaning or birth in comparison to standard-housed controls. EE initiated from birth, but not later, rescued the response of Ten-m3 KOs to the “looming” stimulus (expanding disc in dorsal visual field), suggesting improved visual function. EE can thus induce recovery of visual behaviour, but only during an early developmentally-restricted time-window.